Does the Costless Identification of Contributors Affect the Intuitiveness of Prosocial Behavior? - Rimawan Pradiptyo; Putu Sanjiwacika Wibisana (Journal of Indonesian Economy and Business, 2022)
Introduction/ Main Objectives: This study investigates whether relaxing the assumption of the non-anonymity of participants in an experiment of a finitely repeated public-good game with randomly matched players affects the intuitiveness of prosocial behavior. Background Problems: Various studies show that, in general, participants of social dilemma game experiments tend to be intuitive in choosing prosocial behaviour, whereas non-cooperative behavior tends to be slow. Other studies show that experiments which induced the non-anonymity of participants promote prosocial behavior, however, these studies did not impose non-anonymity on the participants. Novelty: This study aims to fill the literature gap on whether introducing non-anonymity of participants in a social dilemma game experiment may affect the intuitiveness of prosocial behavior. Research Methods: This study used a laboratory experiment of finitely repeated public-good games with randomly matched players in each stage. The main difference between the control and the treatment groups lay in the anonymity of participants in the interaction, where participants in treatment group are exposed to the photo of their opponent. Finding/Results: The results show that relaxing the anonymity setting improved the participants’ contributions to the public-good game; however, their prosocial behavior became less intuitive than non-cooperative behavior. Conclusion: This paper demonstrated an attempt to fill the gap in the literature between the intuitiveness of prosocial behaviour and the role of identity in prosocial behavior.